Re-Inventing Africa's Development Linking Africa to the Korean Development Model - Park, Jong-Dae.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This open access book analyses the development problems of sub-Sahara Africa (SSA) from the eyes of a Korean diplomat with knowledge of the economic growth Korea has experienced in recent decades. The author argues that Africa's development challenges are not due to a lack of resources but a lack of management, presenting an alternative to the traditional view that Africa's problems are caused by a lack of leadership. In exploring an approach based on mind-set and nation-building, rather than unity - which tends to promote individual or party interests rather than the broader country or national interests - the author suggests new solutions for SSA's economic growth, inspired by Korea's successful economic growth model much of which is focused on industrialisation. This book will be of interest to researchers, policymakers, NGOs and governmental bodies in economics, development and politics studying Africa's economic development, and Korea's economic growth model.
Part 1: The Paradox of Sub-Saharan Africa -- 1. Disillusionment and Dilemma -- 2. Assessing the Role of Foreign Aid, Donors and Recipients -- Part 2: Rethinking the Root Causes of Africa's Under-Development -- 3. Review of Conventional Explanations -- 4. Uncovering the Main Root Cause: The Mindset Factor -- Part 3: Africa$1 (Bs Incomplete Nation-Building: What is Missing? -- 5. Finding the Missing Links -- 6. Reasons for Optimism and the Tasks at Hand -- Part 4: Understanding Korean Development Model and Policies -- 7. Korea's Path of Development in Retrospect -- 8. The Essence of the Korean Model of Development -- Part 5: Implications of the Korean Development Model for Africa -- 9. Applicability of the Korean Model of Development for Africa -- 10. Policy Recommendations for Africa -- 11. Engineering Rural Development for Africa -- Part 6: Re-Inventing Africa$1 (Bs Development from the Lessons Learned -- 12. Re-Setting the Priorities -- 13. Enacting a Bold but Harmonious Change.s
Keywords: Development economics; Africa -- Economic conditions; Economic policy; Economic development; Africa -- Politics and government; Development Economics; African Economics; Economic Policy; Economic Growth; Development Studies; African Politics